Vibration Characteristics of Subway Tunnel Structure in Viscous Soil Medium. (8th February 2021) - Ren, Dawei; Shao, Shengjun; Cao, Xiaoshan; Hu, Yifeng
Abstract : Based on research on subway tunnels in a viscous soil medium, this paper establishes the vibration equation of a tunnel structure by using the theory of moderately thick cylindrical shells and the method of wave propagation. The soil around the tunnel is represented in simplified form as an isotropic viscoelastic medium to obtain the equation of motion of the soil, and the vibration control equation of the tunnel under the influence of viscous soil is obtained by coupling. By numerical calculations, the variation trends in the natural vibration frequency of the tunnel and attenuation affected by soil viscosity under different modes are given. Furthermore, the influences of the tunnel radius, wall thickness, and length on the vibration characteristics of a tunnel structure in viscous soil are discussed. This study will provide a reference for the design of subway vehicles and the antivibration design of subway tunnel structures.